THE ROLE OF LAND DEED OFFICIALS (PPAT) IN THE IMPOSITION OF ACQUISITION DUTY OF RIGHT ON LAND AND BUILDING IN THE EXCHANGE PROCESS OF LAND AND BUILDING IN DENPASAR CITY - Dita Paramitha; I Nyoman Putu Budiartha; I Nyoman Sukandia (Warmadewa Press, 2021)
In the process of exchanging land rights, the facts show that the use of market value as the basis for calculating the acquisition duty of right on land and building often creates problems in the field. This study aims to examine the basis for imposing acquisition duty of right on land and building in the process of exchanging land and buildings in Denpasar city and to examine the role of land deed officials and the obstacles faced in the imposition of acquisition duty of right on land and building in the process of exchanging land and buildings in Denpasar city. The method used in this study is an empirical juridical research method. The results of this study showed that (1) the imposition of acquisition duty of right on land and building in the exchange process in Denpasar City is applied with the provisions of Law Number 28 of 2009 concerning Regional Taxes and Regional Levies calculated based on market value. (2) The Land Deed Official has a role in making the deed of exchange and in collecting acquisition duty of right on land and building in the process of exchanging the duties and authorities of the land deed official, namely assisting taxpayers in legal acts of exchange in the process of transferring rights to land and/or buildings from the exchange provider to exchange recipients in accordance with Government Regulation Number 24 of 2016 concerning Amendments to Government Regulation Number 37 of 1998 concerning Position Regulations for Land Deed Maker Officials.